The Tax Categories in Spain and Latin America: Special Consideration of Social Contributions - Pérez Zúñiga, José María (2016)
The concept of tax is not a pacific question, since it demonstrates an analysis of the constitutions and the tributary regulation of Spain and the countries of Latin america. Neither it is the concept of social prices, considered as a tributary category (the special contributions) for the Model of Tributary Code for Latin America, but not for the scientific doctrine.